THE EFFECT OF RELATIONSHIP LEARNING IN DRIVING GREEN INNOVATION, GREEN CUSTOMER CAPITAL AND FIRM’S COMPETITIVE ADVANTAGE - Juniati, Sri; Sinaga, Obsatar; Effendi, Kharisya Ayu; Rashid, Aimi Zulhazmi Abdul (International Journal of Supply Chain Management, 2019)
In this study we are utilizing the advanced methodology of PLS-SEM, the motivation of the current study is to explore the role of relationship learning in driving Malaysian manufacturing industryâ??s prospect of green innovation, customer capital and competitiveness. The selection of the sampled industry is done that established that auto-manufacturing sector possesses higher knowledge intensity, invention & customer driven. Hence, in order to collect sample, the study opted 165 organizations within the industry by sending the questionnaire to the various outlets in all fourteen states of Malaysia. The results of PLS-SEM confirm that green product innovation, green process innovation and green customer capital have significantly and positively influenced by relationship learning. Moreover, the results of structural equation modelling also confirm that, green process innovation has significant and positive effect on green customer capital. However, green product innovation has also a positive and significant impact on green customer capital. Finally, the results further prescribed that green customer capital has a positive and significant effect on competitive advantage. The ultimate model clarifies 57.28% change of competitive advantage by the four factors that are relationship learning, green product innovation, green process innovation and green customer capital.